2017
DOI: 10.1080/2162402x.2017.1376153
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of extracellular vesicles are associated with therapy failure and disease progression in breast cancer patients undergoing neoadjuvant chemotherapy

Abstract: Extracellular vesicles (EVs) have been discussed as a diagnostic tool for minimal residual disease (MRD) evaluation in breast cancer (BC) in addition to the analysis of circulating tumor cells (CTCs). Therefore, we investigated circulating EV levels as surrogate markers for disease monitoring and prediction of prognosis in primary, non-metastatic, locally advanced BC patients. EVs were enriched from blood samples of BC patients before and after neoadjuvant chemotherapy (NACT) and from healthy females. EV marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 33 publications
14
94
0
Order By: Relevance
“…These are described as secreted lipid bilayer-enclosed lumens and are claimed to be valuable reservoirs of liquid biopsy biomarker [156]. EVs (mainly EVs-associated proteins and microRNAs) are proved to be the biomarkers in breast cancer diagnosis [157,158].…”
Section: Therapeutic Roles Of Extracellular Vesicles In Cancermentioning
confidence: 99%
“…These are described as secreted lipid bilayer-enclosed lumens and are claimed to be valuable reservoirs of liquid biopsy biomarker [156]. EVs (mainly EVs-associated proteins and microRNAs) are proved to be the biomarkers in breast cancer diagnosis [157,158].…”
Section: Therapeutic Roles Of Extracellular Vesicles In Cancermentioning
confidence: 99%
“…In breast cancer, Kreger et al found that, compared to those untreated MDA-MB231 cells, the number of exosomes shed by the MDA-MB231 cells increased after paclitaxel treatment [31]. Besides in vitro model, paclitaxel was reported to induce a higher release of exosomes in 4T1-bearing mice and even in breast cancer patients, it was discovered that more exosomes were secreted after post-neoadjuvant chemotherapy as compared to the basal levels by NTA [32,33]. Similar to above mentioned references, our study showed that DDP resistant cells(MGC803/DDP and MKN45/DDP) could release more exosomes than their parental ones.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, regarding the other precipitation-based strategies analyzed in our study, the main advantage of ExoGAG technology is the purity of the EVs obtained, which is a key factor for their posterior characterization. Linked to the extensive literature showing that EVs derived from tumor cell lines contribute to tumor invasion, chemoresistance, angiogenesis, tumor innervation, metastasis or immune escape [21,22], and to those evidences demonstrating that tumor-derived EVs are associated with advanced disease in different indications [23][24][25][26][27][28] and the response to therapy [29], the analysis of EV-based biomarkers should be expedited for the translation of this form of liquid biopsy into the clinics.…”
Section: Discussionmentioning
confidence: 99%